Predicting the Potential Geographical Distribution of Medicinal Plant (Taxus baccata, L. subsp. Wallichiana) in Shimla District, Himachal Pradesh - Kumar, Aman; Sharma, A. K.; Kumar, Rajesh (Indian Forester, 2022)
The population of medicinal plant, Taxus baccata (Himalayan yew) is declining due to over harvesting of its bark and leaves, most wild populations are threatened and are endangered in the Himalaya. As a consequence, the species has already become endangered, facing risk of extinction soon. The present study has been conducted to predict the potential habitats for Taxus baccata in Shimla using the MaxEnt modeling. Through Multi-co linearity test only 19 variables along with 52 Spatio-temporally independent species occurrence locations were used for modeling. IDW method was used to interpolate the soil data. The result shows that the best AUC of 0.971 Â± 0.015 was obtained when the model was set at 100 replication and 1000 iterations. The interpretation of variables revealed that, apart from climatic and topographic parameters, edaphic factor also has influential impact on the distribution of plant. The jackknife test shows that edaphic factor (phosphorus, carbon, nitrogen, pH), topographic and Environmental factor BIO14 (Precipitation of Driest Month) and BIO11 (Mean Temperature of Coldest Quarter) were the key predictor variables associated with its distribution. The success of this model could be promising in determining potential distribution of Himalayan yew and its reintroduction can be useful in the study of species ecology, biogeography, and conservation planning in the Himalaya.